Influência da neuromodulação parassimpática durante a indução da periodontite em camundongos - Santana, Juliana Bueno [UNESP] (2016)
Periodontal disease (PD) is one of the most common infections of human beings, and it is characterized by destruction of tooth supporting tissues, including alveolar bone. Recently it has been shown that the systemic regulation of bone remodeling is also made by two branches of the autonomic nervous system: the sympathetic, favoring bone loss and the parasympathetic, which promotes increase of bone mass. The aim of this study was to verify, through the administration of acetylcholinesterase inhibitors, the effect of parasympathetic neuromodulation in induced periodontitis and bone tissue in mice. Forty male mice were divided into 4 groups: (1) Group Galantamine (G), ten animals with induced PD and treated with 3 mg/ kg/day of galantamine; (2) Donepezil group (D), ten animals with induced PD and treated with 2 mg/kg/day of donepezil; (3) Ligature group (L), ten animals with induced PD; and (4) control group (C). The induction of periodontal disease was carried out with a cotton thread insertion around the lower first molars and the treatment lasted 42 days. On the day of sacrifice, animalsblood samples were collected for serological analysis of nuclear factor-kappaB ligand (RANKL) and osteoprotegerin (OPG). The left hemimandibles were submitted to histomorphometric analysis and the left femur to the three point bending test for assessment of extrinsic and intrinsic properties. The use of the drugs did not reduce alveolar bone loss in treated groups. No statistically significant differences regarding the biomechanical properties of femurs or serum RANKL and OPG were observed. We conclude that galantamine and donepezil, at doses and time used, did not influence the pathogenesis of PD or systemic bone remodeling.